2016
DOI: 10.1093/molehr/gaw026
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic myeloid-derived suppressor cells maintain feto-maternal tolerance by inducing Foxp3 expression in CD4+CD25T cells by activation of the TGF-β/β-catenin pathway

Abstract: This research was supported by the National Natural Science Foundation of China (Grant No. 81270715; 91442113). The authors have nothing to disclose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 48 publications
5
62
0
1
Order By: Relevance
“…Consistent with the published data (Kang et al, , ; Sinha et al, ; A.‐M. Zhao et al, ), our recent studies (unpublished) have confirmed that MDSCs at the mouse maternal–fetal interface is critically involved in the maternal–fetal immunotolerance, and the reduction in the number of MDSCs and decline in their function may lead to the loss of pregnancy.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with the published data (Kang et al, , ; Sinha et al, ; A.‐M. Zhao et al, ), our recent studies (unpublished) have confirmed that MDSCs at the mouse maternal–fetal interface is critically involved in the maternal–fetal immunotolerance, and the reduction in the number of MDSCs and decline in their function may lead to the loss of pregnancy.…”
Section: Introductionsupporting
confidence: 91%
“…Several studies have shown that the accumulation and activation of MDSC are correlated with a successful pregnancy. For instance, it was found that MDSCs percentage is increased in the blood and the placenta of pregnant women (Kang et al, ; Kostlin et al, ). Furthermore, reduced levels of suppressive monocytes in the blood and endometrium in both mice and women are associated with higher incidences of early miscarriage (Nair, Sinha, Khanna, & Singh, ; H. Zhao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also confirmed by functional MDSCs transfer transplantation model [21]. In terms of mechanisms, it has been reported that TGF-β played a central role in MDSCs mediated Tregs induction [93]. In addition to Tregs induction from CD4 + /CD25 − T cells, MDSCs derived TGF-β also offered Tregs plasticity that Th17 cells transdifferentiated into Foxp3 + Tregs [94].…”
Section: Relationships Between Mdscs and Other Immune Cellssupporting
confidence: 65%
“…Before birth, GR-MDSC may play a critical role in maintaining maternal-fetal tolerance [12,13,34,35], being beneficial for fetal life, whereas postnatally elevated GR-MDSC numbers may contribute to postnatal immunosuppression and susceptibility to infections. Before birth, GR-MDSC may play a critical role in maintaining maternal-fetal tolerance [12,13,34,35], being beneficial for fetal life, whereas postnatally elevated GR-MDSC numbers may contribute to postnatal immunosuppression and susceptibility to infections.…”
Section: Gr-mdsc In Preterm Infantsmentioning
confidence: 99%